2019
DOI: 10.1186/s12964-019-0444-1
|View full text |Cite
|
Sign up to set email alerts
|

Induction of LEF1 by MYC activates the WNT pathway and maintains cell proliferation

Abstract: Background While regulated WNT activity is required for normal development and stem cell maintenance, mutations that lead to constitutive activation of the WNT pathway cause cellular transformation and drive colorectal cancer. Activation of the WNT pathway ultimately leads to the nuclear translocation of β-catenin which, in complex with TCF/LEF factors, promotes the transcription of genes necessary for growth. The proto-oncogene MYC is one of the most critical genes activated downstream the WNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 54 publications
(67 reference statements)
0
56
0
1
Order By: Relevance
“…MYC overexpression has been shown to lead to LEF1 transcription, which in turn promotes b-catenin translocation to the nucleus, where it is active. 26 However, in our mouse models, b-catenin could be found in the nucleus, even in the context of low levels of MYC, which suggests a different mechanism, possibly involving suppression of bcatenin-mediated transcription. Expressed independently, MYC promotes proliferation and dedifferentiation, which is observed at the transcriptional and histologic level, while b-catenin is associated with differentiation.…”
Section: Discussionmentioning
confidence: 59%
“…MYC overexpression has been shown to lead to LEF1 transcription, which in turn promotes b-catenin translocation to the nucleus, where it is active. 26 However, in our mouse models, b-catenin could be found in the nucleus, even in the context of low levels of MYC, which suggests a different mechanism, possibly involving suppression of bcatenin-mediated transcription. Expressed independently, MYC promotes proliferation and dedifferentiation, which is observed at the transcriptional and histologic level, while b-catenin is associated with differentiation.…”
Section: Discussionmentioning
confidence: 59%
“…Nevertheless, as expected, an upregulation in phosphorylated β-catenin accompanied with increased phosphorylation of GSK3β demonstrates Wnt inhibition. [39][40][41] Inhibition of pGSK3β, with LY2090314, and subsequent activation of canonical Wnt/β-catenin signaling was confirmed through overexpression of AXIN2 42 and LEF1 33 regardless of prior Wnt inhibition; this was accompanied by significant repression of Wnt inhibitors, sFRP1 and DKK1. This is important when we consider our findings from a prior study 21 where cells remained in a disruptive state, despite removal of Wnt inhibitor, prolonging a pathologic phenotype.…”
Section: Discussionmentioning
confidence: 92%
“…2 B). AXIN2 32 and lymphoid enhancer-binding factor 1 ( LEF1 ), 33 transcriptional target genes for Wnt, were used as markers of Wnt signaling activation. The mRNA expression of both genes were significantly upregulated with Wnt activation after inhibition (6.7-fold, P < 0.001 and 3.7-fold, P < 0.001, respectively) and with activation only (6.35-fold, P < 0.001 and 3.8-fold P < 0.001, respectively) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MYC is related to cell growth arrest and proliferation, thereby contributing to tumorigenesis (58). A previous study showed that knocking down MYC resulted in a reduction in the viability of colon cancer cells (59). In addition, a study indicated that the expression of MYC target genes was inhibited in response to the downregulation of Gcn5 histone acetyltransferase activity, contributing to apoptosis of lymphoma cells (60).…”
Section: Discussionmentioning
confidence: 99%